Studi Berbagai Faktor Yang Berhubungan Dengan Kecemasan Ibu Primipara Menjelang Persalinan Di Ruang Kebidanan RSUD Abunawas Kota Kendari - Amiruddin Amiruddin (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2022)
Anxiety is a response to certain situation that are threatening and is a normal thing that happens accompanied the development and changes. Factors associated with anxiety include psychological factors and knowledge, the mother needs a companion during the process of delivery. Mothers need the support, especially from their husband or their close relatives in order to undergo the process of delivery a baby to feel savely and comfort. The purpose of this study was to determine the relationship between the knowledge and support for families with anxiety primiparous mothers before delivery in the obstetric room in the public hospital Abunawas of Kendari City. This study is a correlational analytic survey research with cross sectional study approach. The population of this study were all primipara mothers who gave birth in the public hospital Abunawas of Kendari City there are 275 mothers. There are 60 mothers as sample of this study were taken by using accidental sampling. The data was processed by using descriptive and inferential analysis technique.The data collection using questionnaires. The result of this study shows that the knowledge has a relationship with anxiety of primiparous mothers, the result was obtained by doing the Chi-Square test with p < 0,05. This is because mothers who lack of knowledge about the delivery process would have a severe anxiety. The results on family support shows that there is relationship between family support and mothers’ anxiety before the delivery process, the result obtained by doing chi square test with p < 0,05.This is because the support from the family is less given to the mothers and causes severe anxiety to the mothers. Because psychologically, the mother needs a companion during the process of delivery the baby. The attention gained by the mothers during the delivery process will always be remembered by the mothers, especially for those who first gave birth and can motivate mothers to have smooth delivery and feel comfortable and safe and not experience anxiety in the delivery process.